PENYALAHGUNAAN WEWENANG HAKIM DALAM MEMBUAT PUTUSAN (Studi Kasus Putusan 464/Pid.B/2017/PN.Tjk.) - Dwi Putri Melati (Universitas Katolik Indonesia Atma Jaya, 2019)
Discrepancies are found in decision No. 464 / Pid.B / 2017 / PN.Tjk, because the panel of judges decapitates or omits an element of article 310 paragraph (2) of the Criminal Code. decisions in accordance with elements of the law and legal remedies for judges who abuse their authority. Approach the problem by using a normative juridical approach (legal research). Judicial Power is the power of an independent state to administer justice to enforce law and justice based on the Pancasila and the 1945 Constitution of the Republic of Indonesia, for the sake of the Republic of Indonesia. But in reality, at the point that explains that there are no consequences for judges in carrying out their duties, it is often used as an opportunity for judges to commit irregularities and be unfair and impartial. if there is an irregularity claimed by the judge in taking the decision of a case, then the injured party can file a complaint to the Supreme Court supervisory body and also the judicial commission. So it is important to create a special team that can impose sanctions on judges who commit irregularities, are not competent, not qualified and unfair in deciding a case.